Intratubular Enterococcus faecalis viability assessment following root canal instrumentation with rotary and reciprocating systems via fluorescence microscopy - Jamileh Ghoddusi; Ehsan Arian; Maryam Golmohammadi; Maryam Gharechahi; Siavash Moushekhian (Tabriz University of Medical Sciences, 2020)
Background. The present in vitro study aimed to compare the effectiveness of the WaveOne and ProTaper Gold systems in removing the Enterococcus faecalis biofilm. Methods. Thirty-eight mandibular premolars were selected. The root canals were assigned to standard control (canals serially enlarged with ProTaper Gold S1-S2-F1-F2, n=15) and experimental (canals enlarged with Primary WaveOne file, n=15) groups. Following the instrumentation procedure, the root canals underwent a sampling procedure, and the colonyforming unit (CFU) counts were determined. The samples were also evaluated under a fluorescent microscope to evaluate viable bacteria. The data were analyzed using independent samples t test and paired samples t test. Results. The results showed that, compared with the ProTaper group, the WaveOne group exhibited the least viable bacteria (P=0.004). Conclusion. It was concluded that comparison with the ProTaper Gold rotary system, the WaveOne reciprocating file is more successful in reducing intratubular viable bacteria counts.